The Role of National and International Intellectual~Property Law and Policy in Reconceptualising~the Definition of Investment - Pratyush Nath Upreti (IIC - International Review of Intellectual Property and Competition Law, 2021)
This article analyses the role of national and international intellectual property (IP) law in assessing IP as a protected investment. It offers two approaches for controlling investment arbitration related to intellectual property rights (IPRs), followed by an examination of the implications and challenges of those approaches. Its main argument is that even if a dispute arises from an investment (IP as an investment), it does not necessarily fall under the jurisdictional requirements of investment arbitration. Rather, assessing IP as an investment must be done by referring to national laws. This is more relevant in the case of IPRs as they are territorial. This means that rights and obligations are derived from national IP legislation. Essentially, only those IPRs that are "protected" by national regimes should be treated as investments. This article also examines the language used in investment agreements and arbitral awards to analyse the role of national law, particularly in determining the validity and scope of IP investments. Then it examines three IP-related arbitral cases to discuss how arbitral tribunals have used national law. Finally, it suggests approaches for controlling investment arbitration by integrating the territoriality principle and the social objectives and bargains achieved through international IP treaties.
Keywords: 340; Investment; ISDS; TRIPS; IIAs~; National law; Arbitration; ICSID; Intellectual property